Effect of fabrication parameters on surface roughness of FDM parts - Kim, Min Kyung; Lee, In Hwan; Kim, Ho-Chan (International journal of precision engineering and manufacturing, 2018)
The FDM (Fused Deposition Modeling) technology is widely used due to its low process cost and good mechanical properties. However, fabricated parts have relatively inferior surface roughness compared to liquid material type process such as SL (Stereolithography). In this research, effects of fabrication parameters such as the gap between nozzle and substrate, inflow speed of filament material and heating moving speed of nozzle on the FDM-fabricated line figuration was investigated experimentally. The extruded line figurations such as width, thickness and cross-sectional shapes were examined. An empirical formula of the line fabrication for fabrication parameters was made based on the experimental results. Moreover, effect of line fabrication distance on the surface roughness was studied.